HABITAT CHARACTERISTICS AND SOME BIOLOGICAL ASPECTS OF GIANT FROG (LIMNONECTES CF. GRUNNIENS) - -, Nasaruddin (Jurnal Veteriner; Vol 9 No 4 (2008), 2008)
The objectives of the research was to described habitat charateristics and reproduction aspects of giant frog (Limnonectes cf. grunniens). Some physico-chemical parameters that characteristic for giant frog habitat i.e. air and water temperatur, relative humidity, dissolved oxygen, free CO2 and NH3 in water were measured. Moreover, the reproduction aspects being observed were gonad characteristics, egg size and form, and sperm density. The results indicated that the giant frog habitat was river stream with physical characteristics as following air temperature : 27o–28oC, water temperature : 24o-26 oC, relative humidity : 83%–87%, water turbidity : 1,2–11,6 nephelometric turbidity unit (NTU), and altitude : 20-40 m above sea level. Furthermore, the suitable water characteristics for the habitat were dissolved oxygen : 7.78.2 ppm, free CO2 concentration = 6.6–8.1 ppm, and free NH3 concentration : 0.5–0.6 ppm. The adult giant frog female generally carried 1461.82 eggs in average per individu with diameter ranging from 1.70–3.10 mm. On the other hand, the sperm density of adult male giant frog was found to be 1,614,898 per mm3 with motility rate of 81.23%.
Keywords: habitat, reproduction, Limnonectes cf. grunniens